THERAPEUTICS OF DIABETIC MACULAR EDEMA THROUGH THE LENS OF AYURVEDA: A CASE REPORT - Sanika Abhay Virkar; Pallavi Jagtap; Mayur Shiralkar; Chandana Virkar; Madhav Madhukar (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Abstract: Prevalence of Diabetes Mellitus (DM) has increased drastically. Diabetic Retinopathy (DR) is associated complication which causes vision loss. Vascular leakage leads to fluid built up in macular region of retina causing Diabetic Macular Edema. Diabetic Macular Edema (DME) is a dreadful complication of Diabetic Retinopathy. According to ayurveda, tridosha along with rakta, sapta dhatu in association with drishtigata patala are involved in manifestation of  prameha janya timira. current management approaches for ayurvedic treatment modalities for Diabetic Macular Edema.Objective: To rescue patient's vision and provide symptomatic relief by ayurvedic management in diabetic macular edema.Material and Method: 63 year old male patient, visited shalakyatantra OPD on 8th may 2018, with diminished vision, black spots in front of left eye since 13 days, known systemic history of diabetes mellitus since 11 years was diagnosed as prameha janya timira and treated accordingly. Result: Blood sugar level was reduced and controlled. Marked symptomatic relief on subjective as well as objective parameters were noted.Discussion: Ayurvedic management in Diabetic Macular Edema offers a promising alternative for significant relief in symptoms, visual improvement and to slow down the disease advancement